ANALYSIS OF STRUCTURAL FEATURES AND EXPLOITATION OF COMBINE HARVESTERS OF CLAAS LEXION 750,760 TERRA TRAC ON HARVESTING OF AGRICULTURAL CROPS - Іванишин, В. В.; Іліяшик, В. В.; Дуганець, В. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
The study deals with basic problems that are associated with the features of exploitation of combine harvesters of CLAAS LEXION 750,760 TERRA TRAC. The analysis of constructions of reaping-machines, sloping chambers, threshing machine, cleaning, system of growing and distributing of uncorn part of harvest shallow, caterpillar working system of combine harvesters of CLAAS LEXION 750,760 TERRA TRAC was made. The structural and technological decisions of reaping-machines, threshing machine, cleaning, system of growing and distributing of uncorn part of harvest shallow are solved, which allow collecting grain crops, soybean, pea, rape with minimal losses. The features of construction and exploitation of the caterpillar working system of combine harvesters of CLAAS LEXION 750,760 TERRA TRAC are considered. On the basis of the conducted analysis of constructions of reaping-machines, sloping chambers, threshing machine, cleaning, system of growing and distributing of uncorn part of harvest shallow, caterpillar working system of combine harvesters of CLAAS LEXION, 750,760 TERRA TRAC, the opportunity of their effective exploitation in the conditions of Podillya region is considered. The findings indicate that using the latter in production conditions will gain positive results, high quality and reliability of work